ADOPSI PETANI TERHADAP INOVASI TANAMAN PADI SAWAH ORGANIK DI DESA MOLOMPAR KECAMATAN TOMBATU TIMUR, KABUPATEN MINAHASA TENGGARA - Welson M. Wangke; Benu Olfie, L. Suzana (Sam Ratulangi University, 2016)
The objective of this research is to know the Innovation Adoption of Organic rice farmers in Tombatu Village Molompar Eastern District o Southeast Minahasa Regency and determine factors underlying farmers to adopt organic farming systems, especially organic rice. The study lasted for 3 (three) months, starting from December 2015 to March 2016. The determination of the territories in which the sample is determined by using the model of purposive sampling. For the research sample was taken 10 percent of the population that is 41 organic paddy rice farmers in the Molompar Village. The results showed that the adoption rate of organic paddy rice high enough that most farmers have implemented or adopted the organic paddy rice; based on the speed of innovation adoption of organic rice paddy, earlyimplemented farmer groups was categorized as the most speed of innovation adoption of organic paddy rice; there is a relationship between the level of age, education, extensive land ownership and income. Younger age, higher education, ownership of land, and the high revenue level tend to be of higher organic rice paddy level of adoption.